Cognitive variables of university students: their relationship with the dedication to study and academic performance: Dedicación al estudio y Rendimiento académico en Universitarios - Barrera Hernández, Laura Fernanda (Consorcio de Universidades Mexicanas A.C., 2020)
This research aimed to empirically test a model to explain the dedication to study and academic performance through cognitive variables of university students, such as self-regulation, future orientation, and learning strategies. One hundred eighty-seven students from a university in southern Mexico participated. In the proposed model, it was predicted that the future orientation, self-regulation, and learning strategies, would influence the dedication to study and the academic performance of the students. The theoretical model was tested through structural equations, and the results showed the goodness of fit indicators, so the data support the proposed relationships. The relevance lies in its integrative nature since the majority of research has measured this relationship through isolated correlations of the variables in question.